The Story of the Prophet Yunus in the Koran and the Bible (Analysis of Julia Kristeva's Intertextual Approach) - Muhammad Imam Syafi’i (al-Afkar, Journal For Islamic Studies, 2025)
This study examines the story of the Prophet Yunus in the Qur’an and the Bible using Julia Kristeva's intertextual approach. This analysis will compare and examine the differences and similarities between the two narratives of the Prophet Yunus. We will analyze the structure, themes, and principles in the two stories of the Prophet Jonah and how they can help us understand the intent and purpose behind the stories. In the Koran, the story of the Prophet Yunus is told in Surah Yunus and several other verses. This story tells of the Prophet Jonah who was sent by God to preach to the people of Nineveh, but he ran away and was eventually swallowed by a big fish. This story then ends with the Prophet Jonah repenting and returning to preach to the people of Nineveh. In the Bible, the story of the Prophet Jonah is told in the Book of Jonah. This story also tells of the Prophet Jonah who was sent by God to preach to the people of Nineveh, but he ran away and was eventually swallowed by a big fish. However, the story in the Bible has several experiences with the story in the Koran, such as the story of the Prophet Jonah who was angry and disappointed with God for not allowing him to punish the people of Nineveh. By using Julia Kristeva's intertextual approach, we can compare and examine the differences and similarities between the two narratives of the Prophet Jonah. The results of this study show that the story of the Prophet Yunus in the Koran and the Bible has several differences and similarities, but both have the same goal, namely to remind humans about the power and mercy of Allah. In this case, the Qur'an applies intertextual principles to the Bible, namely haplology, modification, expansion, existence, conversion and parallel.